Digital Accounting Information System Implementation at BPKAD SAMOSIR District - Kuras Purba; Rimky Mandala Putra Simanjuntak; Sahala Purba (Jurnal Akuntansi, 2024)
Problems at BPKAD Samosir Regency evolved over time with the changing landscape of information technology. Initially, BPKAD relied on Microsoft Office Excel software. However, with technological advancements, Microsoft Office Excel was superseded by e-finance applications. The e-finance application played a crucial role in supporting financial activities, particularly accounting, and was in use from 2019 until the conclusion of 2020. In early 2021, a further enhancement occurred as the SIPKD application (Regional Financial Management Information System) took over the role from the previous e-finance application. The aim of this research is to identify and analyze the factors that influence, either partially or simultaneously, the implementation of the Computer-Assisted Accounting System in the management of assets and finances of Samosir Regency. To conduct this research, researchers used quantitative methods with primary data, by distributing questionnaires to Samosir Regency BPKAD employees. Research participants are public service employees and honorary BPKAD Samosir Regency employees who have worked for at least two years and have made a direct contribution to the implementation of the Informal system. The research was conducted between March and April 2023. The results showed that the application of personal technical skills, user involvement, accounting expertise, and superior assistance had a positive and significant impact on the implementation of computerized accounting information systems, while training and education did not have a positive or significant impact on the implementation of information systems. computerized accounting. Human Resources Management plays a crucial role in the successful implementation and operation of Computerized Accounting Information Systems (CAIS) within an organization. This paper examines the key factors that influence the effective utilization of CAIS, including Personal Technical Ability, User Involvement, Training and Education, Accounting Knowledge, Leadership Support, and the Application of CAIS. The recommendation from this research is to add other variables outside the variables that have been researched, such as Good Government Governance, Use of Information Technology, and others. and conducting in-depth interviews regarding the advantages and disadvantages of implementing a computerized accounting information system. As well as adding references and expanding research objects such as all SKPD in Samosir Regency.